2022
DOI: 10.1186/s12889-022-14457-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in self-reported and accelerometer-measured physical activity among pregnant TRICARE Beneficiaries

Abstract: Background Physical activity is recommended for all pregnant individuals and can prevent excessive gestational weight gain. However, physical activity has not been assessed among military personnel and other TRICARE beneficiaries, who experience unique military lifestyles. The current study assessed physical activity among pregnant TRICARE beneficiaries, both active duty and non-active duty, as measured by accelerometry and self-report data to examine potential predictors of physical activity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
2
3
Order By: Relevance
“…In addition, individuals involved in behavioral intervention research reported the pandemic made it more difficult to engage in recommended health behaviors (Cardel et al, 2020 ). In contrast to this previous literature and our hypotheses, however, we found that participants in this study had slightly lower, albeit non-significant, GWG during the COVID pandemic, which could have been due to the high level of exercise in this population (Pebley et al, 2022 ) and potentially extra time to exercise and cook at home during the pandemic. In addition, we also demonstrated that some research studies, like the current study, may have better retention and remained just as effective during the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, individuals involved in behavioral intervention research reported the pandemic made it more difficult to engage in recommended health behaviors (Cardel et al, 2020 ). In contrast to this previous literature and our hypotheses, however, we found that participants in this study had slightly lower, albeit non-significant, GWG during the COVID pandemic, which could have been due to the high level of exercise in this population (Pebley et al, 2022 ) and potentially extra time to exercise and cook at home during the pandemic. In addition, we also demonstrated that some research studies, like the current study, may have better retention and remained just as effective during the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…International guidelines for PA practice during pregnancy recommend that all pregnant women without medical contraindication should perform at least 150 min of moderateintensity activity per week [12,47,48]; these recommendations were met by 67.7% of the pregnant women. These values are lower than those observed during the French PPAQ validation study for pregnant women with obesity [18] and in the Pebley et al ( 2022) [49] study, where it was reported that 100% and 99% of participants, respectively, complied with the recommendations of PA practice. This may be because the sample in the present study used the accelerometer for an average of 678 min per day (approximately 11 h), while participants in the other studies [18,49] used accelerometers for 24 h, thus promoting higher values of time used.…”
Section: Discussioncontrasting
confidence: 62%
“…These values are lower than those observed during the French PPAQ validation study for pregnant women with obesity [18] and in the Pebley et al ( 2022) [49] study, where it was reported that 100% and 99% of participants, respectively, complied with the recommendations of PA practice. This may be because the sample in the present study used the accelerometer for an average of 678 min per day (approximately 11 h), while participants in the other studies [18,49] used accelerometers for 24 h, thus promoting higher values of time used.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Although the direct impact of GWG on military fitness test performance is unknown, women tend to have significantly lower fitness test scores after pregnancy [4,19]. PPWR is a major concern for military leaders and health care providers because it likely negatively impacts returning to pregravid fitness levels and also places women at higher risk for negative health outcomes in subsequent pregnancies because of higher body mass index (BMI) [20,21]. Furthermore, PPWR is associated with long-term maternal overweight/ obesity [22,23], a more broad, significant concern for the DOD and the health care system because of the rapid turnover.…”
Section: Introductionmentioning
confidence: 99%